Varicella-zoster virus glycoprotein expression differentially induces the unfolded protein response in infected cells - Carpenter, John E.; Grose, Charles (Frontiers in Microbiology, 2014)
Varicella-zoster virus (VZV) is a human herpesvirus that spreads to children as varicella or chicken pox. The virus then establishes latency in the nervous system and re-emerges, typically decades later, as zoster or shingles. We have reported previously that VZV induces autophagy in infected cells as well as exhibiting evidence of the Unfolded Protein Response (UPR): XBP1 splicing, a greatly expanded Endoplasmic Reticulum (ER) and CHOP expression. Herein we report the results of a UPR specific PCR array that measures the levels of mRNA of 84 different components of the UPR in VZV infected cells as compared to tunicamycin treated cells as a positive control and uninfected, untreated cells as a negative control. Tunicamycin is a mixture of chemicals that inhibits N-linked glycosylation in the ER with resultant protein misfolding and the UPR. We found that VZV differentially induces the UPR when compared to tunicamycin treatment. For example, tunicamycin treatment moderately increased (8-fold) roughly half of the array elements while downregulating only three (one ERAD and two FOLD components). VZV infection on the other hand upregulated 33 components including a little described stress sensor CREB-H (64-fold) as well as ER membrane components INSIG and gp78, which modulate cholesterol synthesis while downregulating over 20 components mostly associated with ERAD and FOLD. We hypothesize that this expression pattern is associated with an expanding ER with downregulation of active degradation by ERAD and apoptosis as the cell attempts to handle abundant viral glycoprotein synthesis.